2018
DOI: 10.1101/287821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct estimation of mutations in great apes reveals significant recent human slowdown in the yearly mutation rate

Abstract: The human mutation rate per generation estimated from trio sequencing has revealed an almost linear relationship with the age of the father and the age of the mother. The yearly triobased mutation rate estimate of ~0.43x10 -9 is markedly lower than prior indirect estimates of ~1x10 -9 per year from phylogenetic comparisons of the great apes. This suggests either a slowdown over the past 10 million years or an inaccurate interpretation of the fossil record.Here we use sequencing of chimpanzee, gorilla and orang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Our estimates of the Ti:Tv and SW:WS ratios at 0.96 and 1.24 each are also lower than values found in other animals. For instance, the Ti:Tv ratio found in previous pedigreebased studies in other species varied between 1.97 and 2.67 (Agier and Fischer, 2012;Assaf et al, 2017;Besenbacher et al, 2019;Kong et al, 2012;Smeds et al, 2016;Thomas et al, 2018;Venn et al, 2014). Our finding of a lower Ti:Tv ratio is likely a consequence of the relatively low number of C>T transitions at CpG sites.…”
Section: The Mouse Lemur Mutation Spectrumcontrasting
confidence: 41%
See 2 more Smart Citations
“…Our estimates of the Ti:Tv and SW:WS ratios at 0.96 and 1.24 each are also lower than values found in other animals. For instance, the Ti:Tv ratio found in previous pedigreebased studies in other species varied between 1.97 and 2.67 (Agier and Fischer, 2012;Assaf et al, 2017;Besenbacher et al, 2019;Kong et al, 2012;Smeds et al, 2016;Thomas et al, 2018;Venn et al, 2014). Our finding of a lower Ti:Tv ratio is likely a consequence of the relatively low number of C>T transitions at CpG sites.…”
Section: The Mouse Lemur Mutation Spectrumcontrasting
confidence: 41%
“…CpG sites have generally been found to have higher mutation rates relative to other site classes, a pattern discovered several decades ago using DNA sequence comparisons (Bird, 1980a) and ascribed to the frequent deamination of methylated cytosines (Friedberg et al, 2005). Only a four-fold enrichment of mutations at CpG sites (8 mutations, 8.7% of all mutations) was found in mouse lemur, which is less than the at least ten-fold enrichment (12-25% of total mutations) found in other primate studies (Besenbacher et al, 2019;Gao et al, 2019;Thomas et al, 2018;Venn et al, 2014).…”
Section: Low Numbers Of Mutations At Cpg Sitesmentioning
confidence: 87%
See 1 more Smart Citation
“…6,7; Supplementary Table 5). These high-confident DNMs can be explained by the spontaneous mutation rates of primates (0.98~2.17×10 -8 per nucleotide per generation) with 22~78 expected DNMs per generation 27,28 . Consistently, we saw no correlation between the number of high-confident DNMs and the Cas9-editing efficiency (R 2 =-0.140, P=0.765, Pearson's correlation test).…”
mentioning
confidence: 99%
“…Recent mutation rate studies have also suggested significantly slower annual rates than previously estimated (Besenbacher et al . 2018; Scally 2016) which would consequently push back divergence dates such as those discussed by Allen and O'Connell (2020). While these rate studies are based on genome‐wide calculations, and not focused on mitochondrial DNA (Tobler et al .…”
Section: Commentsmentioning
confidence: 89%